Compensating Associates for Supervising Dental Hygiene Production in U.S. General Dental Prac-tices: A Discussion of a Frequently Taboo Topic - David Dunning; Brian Lange; Robert Madden (Wolters Kluwer Medknow Publications, 2010)
Many associateship employment contracts in U.S. general dental practice, probably about 85% based on our review of over 100 contracts in the past decade, are silent about a key issue in associate-ships--namely, compensating associates for supervising dental hygiene production. Not addressing this issue raises ethical questions as well as concerns about professional liability regarding the super-vision of dental hygiene. The associate and owner need to in-clude in an employment agreement what compensation will be given to the associate for supervising dental hygiene production. Compensating associates for supervising dental hygiene production will certainly have a financial impact on the practice. However, direct-ly addressing the issue will allow the owner to manage the financial impact on the practice while also providing a more mutually beneficial employment experience. The associate and owner-dentist need to discuss thoroughly and openly what compensation options are available, if any, to the associate for supervising dental hygiene production. In turn, these should be incorporated in an employment agreement. Five specific compensation strategies are suggested for managing this issue, ranging from production credit for periodic examinations fees and/or radiographs, to compensation for a set amount for each hygiene patient supervised, to profit-sharing based on a pro-rated basis of supervised hygiene production. Successful associateship ar-rangements, including those intended to lead to future practice buy-in or buy-outs, depend in large part of meeting mutual expectations of both parties. Compensating associates for supervising dental hygiene production is a seldom discussed but vitally important issue to manage.